INTERNATIONAL RELATIONS AND WATER MANAGEMENT BETWEEN THE REPUBLIC OF UZBEKISTAN AND THE ISLAMIC EMIRATE OF AFGHANISTAN - Makhmatkulov, Javohir (International Journal of Business, Law and Political Science, 2024)
This article analyzes and predicts the relation between Uzbekistan and Afghanistan according to Realism, Liberalism, and Constructivism theory. Besides, this article focuses more on the Qosh Tepa Canal and its impact on future relations between Uzbekistan, Afghanistan, and Turkmenistan